Financial Inclusion in Tunisia : Low-Income Households and Micro-Enterprises - World Bank Group (Washington, DC, 2015)
This technical note provides a snapshot of financial inclusion trends and challenges in Tunisia. It follows the recent expiration of the Coordinated Vision for the Development of Microfinance in Tunisia 2011-2014, national strategy published in 2011. This document does not examine all aspects of financial sector development, but rather concentrates specifically on financial inclusion for low-income households and micro-enterprises.